Accuracy and immersion improvement of hybrid motion capture based real time virtual validation - Bönig, Jochen; Fischer, Christian; Weckend, Holger; Döbereiner, Florian; Franke, Jörg (Procedia CIRP, 2014)
Using a digital human model for dynamic analysis is due to the high modelling complexity in digital environments not very prevalent. The movement of the worker is either unrealistic, or time-consuming to realize. Therefore, the need for research is a time saving possibility to explore virtual validation by a human model taking advantage of a nonetheless realistic movement design. To achieve this goal, we use an experimental setup including both a hybrid motion capture system and an interface for the connection to digital validation software. The motion capturing in connection along with the validation software allows real time modelling respectively tracking and therefore a realistic movement of the human model. To get good results while applying the motion capturing approach in mixed reality situations, it is necessary to have an exact registration between the real and virtual environment. Hence, the experimental setup must be designed for both. The key challenge here is to superimpose the CAD data with the real objects used for haptic feedback and better immersion. To realize an optimal registration we use a laser tracker solution.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Assembly; Mixed reality; Simulation

Creating realistic human model motion by hybrid motion capturing interfaced with the digital environment - Bönig, Jochen; Perret, Jerome; Fischer, Christian; Weckend, Holger; Döbereiner, Florian; Franke, Jörg (FAIM 2014 - Proceedings of the 24th International Conference on Flexible Automation and Intelligent Manufacturing: Capturing Competitive Advantage via Advanced Manufacturing and Enterprise Transformation, 2014)
A key challenge in production engineering projects is to achieve significant time and cost savings through early validation of manual assembly operations. Nevertheless, the use of digital human models for dynamic analyses is not very prevalent because of the high modeling complexity in the digital environment: with existing simulation tools, the worker's motions are either unrealistic or too time-consuming to program. Hence, further research is needed for developing a time-saving and realistic human motion simulation. In this article, we present an experimental setup for the early validation of manufacturing tasks through interactive simulation. We use a new hybrid motion-capture system interfaced with the digital environment, which facilitates the generation of realistic human model motion in real time. The software platform used is DELMIA V5. The article describes the relationship between optical and inertial tracking, and how the drift of the inertial sensors can be compensated by using a kinematic chain with a human model. Sequences of postures can be saved, both for the human model and tools, and later replayed synchronously. Finally, we detail the use of our setup in a real-world scenario within automotive manufacturing. This article acts as a practical contribution to simulation-based Manufacturing Ergonomics and Human Factors, illustrating the effectiveness of state-of-the-art technology for viable cost and time savings.
CRIS-Team Scopus Importer:2023-03-07

Explicit dynamics process simulation of linear coil winding for electric drives production - Bönig, Jochen; Bickel, Benjamin; Spahr, Michael; Fischer, Christian; Franke, Jörg (2014 4th International Electric Drives Production Conference, EDPC 2014, 2014)
Slowly but steadily, more and more electric vehicles push onto the consumer market. For a cost efficient production of electrical engines, in first-class quality and in sufficient quantity, it is indispensable to understand the process of coil winding. Thereby the prediction of the wire behavior is one of the key challenges. Therefore, a detailed model is built to investigate wire behavior during the linear winding process. The finite element based simulation tool LS-DYNA serves as explicit dynamics tool. To represent the high dynamic process of winding within this simulation, some first adaptions have to be made. This means, that dynamic influences such as rotational speed or acceleration of the coil body are definable. Within process simulation, the given boundary conditions are applied to the model. The material properties of the wire under scrutiny are validated by a tensile test and by the values out of datasheets in previous research. In order to achieve the best convergence, different contact algorithms are selected for each individual contact behavior. Furthermore, specific adjustments to the mesh are necessary to gain significant results. State of the art in coil winding is an experimental procedure, which delivers adequate process parameters and, thus, expertise in winding technology. Nevertheless, there are a lot of different, interacting parameters, which have to be optimized in terms of boundary conditions. The simulation model of winding process, in which varying parameters can be optimized pertaining to the optimal winding result, calls for extensive research in this field. The generated model enables the user not only to influence the process parameters but also to modify the geometry of a winding body. To make the simulation scientifically sound, it is validated by previous experiments and simulations
Keywords: coil winding; Explicit dynamics; simulation

Explicit FEM analysis of a new contacting method for electronic devices with novel wiring harnesses - Spahr, Michael; Bönig, Jochen; Gläßel, Tobias; Spreng, Simon; Ebert, T.; Franke, Jörg (61st IEEE Holm Conference on Electrical Contacts, HOLM 2015, 2015)
Through customers' desire for an individualization of vehicles, new electronics-supported functions are continuously being added. The automobile wiring harness must meet these requests without any further increase of weight and volume. The basic trend towards a modular vehicular design, the continually growing complexity of production and assembly processes, supports the use of flexible flat cables (FFCs) in a hybrid wiring system architecture. For an integral approach, it is also important to develop corresponding alternatives for electrically contacting FFCs with the components. To that end, the process-conditional, one-sided accessibility of FFCs represents a particular challenge. Motivated by these challenges, the Institute FAPS has developed an automated assembly system of FFCs and a new concept for a flexible electric contacting system enabling direct electrical contacting of installed FFCs. The scope of this approach is the analysis of the new contacting method by means of an explicit finite element analysis (FEA). For this purpose, a numerical model was developed that enables the simulation and optimization of the contacting process and its important parameters. In a second step, the results of the FEA are validated by respective experiments.
Keywords: contact area; contact force; contact resistance; electrical contact; finite element modelling; flexible flat cable

Planning and simulation of high-voltage energy storage assembly for automotive industry - from scalable product concepts via assembly planning and material flow simulation through to web-based assembly information - Bönig, Jochen; Fischer, Christian; Brandmeier, Markus Andreas; Mersdorf, Thorsten; Braun, Thomas; Mrugalla, Claudia (2013)
Electric mobility technologies are part of the future concept to reduce the emissions of greenhouse gases and thus to counteract the global warming. Although the idea of using electricity as drive energy came up in the 19 century, a considerable potential of development still remains. The automotive industry is in the midst of a time of transition, in which business may change fundamentally in order to meet the upcoming conditions. The current major challenge of e-mobility is the high-voltage battery, modern vehicle concepts focusing on. A technology that offers a high potential is the lithium ion technology. One main problem is the missing expertise in production of battery systems including the new requirements, e.g. working safety and high diversity of variants. The purpose of this paper is to analyse the production process of these storage systems regarding both concepts for managing variability for the overall production process as well as an in-depth planning of assembly. The paper scrutinizes the challenges arising from the manufacturing of storage systems on the basis of a purpose-designed demonstrator battery. In this regard the production planning process is represented by creating a virtual assembly line. Against this background different scenarios are built in order to examine the impact of various battery forms with their variety of influencing factors. Furthermore, the impact of the future's demand for high-voltage batteries on the capacity of the assembly line is to be scrutinized. For this purpose a simulation considering the influence of demand fluctuations on cycle times and buffers is built up and conducted. Eventually, the paper outlines a way of reusing the created data for an assembly information system. © (2013) Trans Tech Publications, Switzerland.
Keywords: Assembly information system; Modular design; Simulation

Shortening innovation cycles by employee training based on the integration of virtual validation into worker information systems - Fischer, Christian; Lusic, Mario; Bönig, Jochen; Hornfeck, Ruediger; Franke, Jörg (Procedia CIRP, 2015)
Due to rapid developments in technology, the complexity of assembly processes has increased. To meet these challenges, effectively qualified workers are necessary. A worker must have a basic education to understand new training content and be able to translate it into daily work. Also, a fast and efficient data flow from innovations within product development to training is necessary. Especially the use of three-dimensional design data has a great immersion effect for training candidates. The newly learned content is more memorable in comparison to teacher-centered education in schools. We present a solution using a worker information system for this kind of electronic learning. This system may be used even in advance of production. This concept can be extended by providing qualification or even educational content. Using multimedia data derived from computer-aided design and virtual validation, our approach for a novel training concept can be realized.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Assembly; Digital Manufacturing System; Information; Learning

Simulation of orthocyclic windings using the linear winding technique - Bönig, Jochen; Bickel, Benjamin; Spahr, Michael; Fischer, Christian; Franke, Jörg (5th International Conference on Electric Drives Production, EDPC 2015, 2015)
A continuously rising number of electric vehicle licensing is mentioned since the last few years in Germany. For a cost-efficient production of electrical engines in first-class quality and in sufficient quantity, it is indispensable to understand the process of coil winding. Thereby, the prediction of wire behavior is one of the key challenges. Therefore, a detailed model is built to investigate wire behavior during the linear winding process. The finite element based simulation tool LS-DYNA serves as explicit dynamics tool. The tool works with an explicit time integration method for time discretization. To represent the high dynamic process of winding within this simulation, dynamic influences such as rotational speed or acceleration of the coil body are definable. Within process simulation, the given boundary conditions are applied to the model. The non-linear material properties of the wire are validated under scrutiny by a tensile test and by values out of datasheets in previous research work. Simulation results of orthocyclic windings using the linear winding technique are presented within this paper. The dynamic simulation model is validated by experiments using the caster angle of the wire guide as reference parameter. The caster angel rises during the winding process of the first layer until the wire jumps to the next layer. Hence, it is possible to identify the maximum caster angle and match the simulation value against the experiment value. The travel profile of the wire guide is identified as extremely important to generate an orthocyclic winding. Another substantial part is the wire fixation respectively the geometry to support the first winding offset from winding one to winding two. Results of orthocyclic windings are simulated with and without grooves on the coil body surface and demonstrate the positive influence of grooves for an accurate orthocyclic winding picture.
Keywords: Explicit dynamics; linear winding; simulation

Structural mechanic finite element analysis of the bend and torsion behavior of high-voltage cables - Bönig, Jochen; Spahr, Michael; Fischer, Christian; Franke, Jörg (3rd International Electric Drives Production Conference, 2013)
The use of electric power systems in automobiles represents a massive change in the production line of car manufacturers. To guarantee an efficient and at the same time damage free installation of the current carrying high-voltage cables, virtual validation of assembly operations makes an important contribution. On the market available simulation tools like IC:IDO Flexible II, IPS Cable Simulation and TEA Pipe compute the rigidity of the cable system by using substituted material properties. The high-voltage cable producers don't provide these substituted parameters. Measuring the properties during a physical experiment is inefficient because of the high time exposure and costs. The complex structure of the high-voltage cables and the high number of variants lead to the advantage of simulation opposite experiment. So the need for research is a finite element model to generate the necessary substituted material properties in a time and cost efficient way. To achieve this goal, bend and torsion tests of detailed cable models are simulated and matched with experimental results for validation. Under the premise of the plastic material behavior of the wire and the interface friction between the individual cable components, different mesh strategies are evaluated. The performance of beam against solid element meshed wires is crucial and the element size influence to the result quality is researched. For a robust convergence the complex contact problem is mapped by the Augmented-LaGrange algorithm and the fitted contact stiffness between the individual cable components. The results are the influence of the plasticity and the interface friction to the change of the stiffness properties depending on the cable load.
Keywords: E|DRIVE; E|SYS; Simulation

Structural mechanics process simulation of linear coil winding - Bönig, Jochen; Bickel, Benjamin; Ebenhöch, Matthias; Spahr, Michael; Fischer, Christian; Franke, Jörg (Trans Tech Publications Ltd, 2014)
Slowly but steadily, more and more electrical vehicles push onto the consumer market. To produce electrical engines cost efficiently, in first-class quality and in sufficient quantity, it is indispensable to understand the process of winding. The prediction of the wire behaviour is one of the key challenges of coil winding. It is sophisticated and sometimes impossible to measure relevant process parameters (like the wire pull force after wire guide, the wire stress after deformation) in experiments in order to be able to investigate the process in detail. Therefore, a detailed model is built to simulate the wire behaviour during linear winding process. The finite element based simulation tool ANSYS Workbench® serves as the static structural component tool. ANSYS provides comprehensive possibilities in structural mechanics and it is possible to simulate thermal and electrical physics for future work (Co-simulation within one tool). To represent the high dynamic process of winding within this simulation, some first adaptions have to be made. This means, that dynamic influences such as rotational speed or acceleration of the coil body are neglected. Within static structural analysis, the given boundary conditions are applied to the model. The material properties of wires under scrutiny are validated by a tensile test and by the values of datasheets. In order to achieve the best convergence, different contact algorithms are selected for each individual contact behaviour. Furthermore, some adjustments to the mesh are necessary to gain significant results. State of the art in coil winding is an experimental procedure, which delivers good process parameters and, thus, expertise in winding technology. However, there are a lot of different, interacting parameters, which have to be optimized in terms of boundary conditions. The simulation model of the winding process, where varying parameters can be optimized pertaining to the optimal winding result, calls for extensive research in this field. The generated model enables users not only to influence the process parameters but also to modify the geometry of the winding body. To make the simulation scientifically sound, it is validated by experiments.
Keywords: Coil winding; Simulation; Structural analysis

Virtual validation of the manual assembly of a power electronic unit via motion capturing connected with a simulation tool using a human model - Bönig, Jochen; Fischer, Christian; Brossog, Matthias; Bittner, Martin; Fuchs, Markus; Weckend, Holger; Franke, Jörg (Smart product engineering, Proceedings of the 23rd CIRP Design Conference, 2013)
A key challenge for gaining important time and cost potentials in production engineering projects is an early virtual validation during the pre-series. Under the premise to replace physical by digital mock-ups, we will present requirements and solutions of a virtual validation focused on manual assembly of power electronics in automotive industry. Using a digital human model for dynamic analysis is not very prevalent, because of the high modeling complexity in the digital environment. The resulting motions of the human model are furthermore unrealistic. Hence the need for research is a time saving and, regardless, a realistic movement design for virtual validation by a human model. To achieve this goal, we use an experimental setup including a variable eight camera motion capture system, a data glove and an interface for the connection to the digital validation softwar
Keywords: human model; Motion Capture System; Simulation; virtual validation

Webbasierte Werkerinformationssysteme: Datenaufbereitung und -darstellung für die Werkerführung im Global Cross Enterprise Engineering - Fischer, Carina; Lušić, M.; Bönig, Jochen; Hornfeck, R.; Franke, Jörg (wt Werkstattstechnik - Online, 2014)
Globalization does not only affect enterprises in areas such as processing and transportation of material goods, but also with a view to the associated data flows. Distributed data generation and processing places higher demands on data fusion and local use. Especially product development data have to be made available for production planning and execution in a timely, efficient and targeted way. This paper presents an approach for use in manual assembly in the field of electromobility.
CRIS-Team Scopus Importer:2023-03-07

Worker Information Systems: State of the Art and Guideline for Selection under Consideration of Company Specific Boundary Conditions - Lusic, Mario; Fischer, Christian; Bönig, Jochen; Hornfeck, Ruediger; Franke, Jörg (Procedia CIRP, 2016)
Due to customer specific products, the number of product variants and the complexity of assembly processes increase. To meet these challenges, worker information systems are used to manage information diversity in manual assembly and to provide the right information at the right time in a lean way. Such systems are available in various types and their classification depends on a particular point of view. In order to enable a holistic overview of the existing diversity, this paper summarizes such systems and their benefits. For this purpose, available categories are shown. Accordingly, this paper serves as a summarizing report for the state of the art. Furthermore, the implementation and configuration of worker information systems depend on company specific boundary conditions. Considering them, a guideline is presented for the selection of worker information systems.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Assembly; Information; Worker information system

Worker information system to support during complex and exhausting assembly of high-voltage harness - Fischer, Christian; Bönig, Jochen; Franke, Jörg; Lusic, M.; Hornfeck, R. (2015 5th International Conference on Electric Drives Production, EDPC 2015 - Proceedings, 2015)
There are a lot of different kinds of electric drives and each category has a different installation position within a vehicle. A huge number of variants pose a challenge for manual assembly as the varying constellations of high-voltage (HV) cables require individual assembly steps. A worker needs information both about a vehicle and about HV components with their properties. We obtained good results for this on base of a worker information system (WIS). We can visualize parts assembly using three-dimensional (3-D) objects. The results of hazard analysis are shown in text format. But a WIS lacks in representing the physical behavior of parts within assembly. Especially HV cables move in an undetermined way when they are handled. We have an approach to simulate HV cables within assembly simulation. The material properties of HV cables during distortion are calculated in a finite element analysis (FEA). These parameters flow into an assembly simulation containing flexible parts like HV cables and a digital human model. The results of simulation runs can not only be used for assembly planning but also for worker guidance. We present an approach how to qualify simulation results for import to a WIS. In addition, possible application scenarios for such a WIS are explained.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Assembly Technologies; Worker Information System